The effect of human resources capacity, budget planning, political budgeting, and public transparency on the of APBD documents and KUA-PPAS’s synchronization in Musi Banyuasin district government - Mat Syuroh, (Technium Social Sciences Journal, 2020)
This study aims to determine the effect of human resources capacity, budget planning, political budgeting, and public transparency on the synchronization between Regional Revenues and expenditures budget (APBD) document and General Policy of Regional Revenues and Expenditures Budget (KUA) and Provisional Budget Ceiling Priority (PPAS) document. The population in this study was councilors and officer/staff involved in the preparation of the Work Plan Budget (RKA) SKPD includes 33 SKPD. The sampling method used census method, where all the population became the samples is 127 peoples. The data in this study using primary data. The data obtained were analyzed through multiple linear regression tests. Hypotheses simultaneously and partially tested by F test and t test. Results of this study showed that simultaneous variable capacity of human resources, budget planning, political budgeting, and public transparency has a positive and significant impact on the synchronization between APBD documents and KUA-PPAS documents. In partial, the capacity of human resources, budget planning, political budgeting, and public transparency has appositive and significant impact on the synchronization between APBD documents and KUA-PPAS documents. The implications of this research can be useful as a conceptual contribution to policy makers, especially in West Lombok Regency Government and Parliament, in which they should be more consistent and have a high commitment dealing with budgeting and KUA-PPAS.